Response-Inhibition Capacity and Short-Term Memory are Robust to the Effects of High Fat Diet (HFD) during Pre and Periadolescence (2014)
Several lines of evidence demonstrate that high fat diet exposure can be detrimental to cognition across the lifespan. We have previously shown that context-stimulus learning is sensitive to high fat diet effects during adolescence but not adulthood. In the present study we determined if pre and periadolescent high fat diet exposure interferes with response-inhibition capacity, rule- learning, and memory during adulthood. Rats were fed a high fat or low fat diet during pre and periadolescence and completed behavioral testing as adults to assess response-inhibition capacity and reinforcer efficacy rule-learning and short-term memory. Results indicate pre and periadolescent high fat diet may have long-term effects on reinforcer efficacy and sustained attention. However, results indicate that either the pre and periadolescence period is too short for a high fat diet to induce long-term deficits in response-inhibition, rule-learning, or memory, or that maturation in the absence of a high fat diet rescued these deficits.